TAKSASI PRODUKSI DAN ANGKA PERAPATAN PANEN PADA TANAMAN KELAPA SAWIT DI KEBUN CIKABAYAN IPB BOGOR - Intae, Ananta Firdaus; Kusumawardani, Eni; Nur Agustin, Jelita (Jurnal Ilmiah Mahasiswa Fakultas Pertanian, 2024)
Pre-harvest production estimation of oil palm is needed to determine the need for labor and facilities related to harvesting activities. The research was conducted at the Cikabayan Farm, Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University. The activity aimed to evaluate the accuracy of the estimation of the real results of fresh fruit bunch production. Estimated production is influenced by plant population per ha, harvest density, and average basket weight. The average estimated harvest density rate was 5.1% and the fresh fruit bunch weight was 13 kg. The accurate estimated value was influenced by the accuracy of the harvest density observation. This shows that the calculation of harvest density and fresh fruit bunches with the peak harvest month and low harvest month. The accuracy of the estimation calculation is influenced by the accuracy of the harvest density observation and the determination of the right fresh fruit bunches.